FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN INFORMASI AKUNTANSI DI INTERNET OLEH PEMERINTAH DAERAH - Rahmad Dian Afryansyah; Haryanto Haryanto (Diponegoro Journal of Accounting, 2013)
The aim of this research is to examine factors which predicted the level of accounting information disclosure in internet by local government. Factors which are going to be tested are size, investment level, wealth, political competition and press visibility. The population of this research are local governments of Indonesia. The number of samples is 47, calculated using Slovin  calculation formula. Analysis method used to test hypothesis in this research is linear regression. The result of this study indicates that press visibility significantly has negative influence to the level of accounting information disclosure in internet by local government. It means that the local government resistance to provide accounting information to the media because the media's tendency is usually to explore the negative side of a local government such as the budget deficit and corruption. The other factors, such like size, investment level, wealth, and political competition do not influence the level of accounting information disclosure in internet by local government significantly.